2008
DOI: 10.1007/s10552-008-9214-x
|View full text |Cite
|
Sign up to set email alerts
|

Meat intake and bladder cancer risk in a Swedish prospective cohort

Abstract: These results do not support the hypothesis that intake of red meat, processed meat, poultry, or fried meats/fish is associated with the risk of developing bladder cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…Nitrosamines have been shown to cause a wide range of tumors, including cancer of the bladder, in more than 40 animal species (3). Intake of red meat (the most important source of heme iron) has shown inconsistent results with bladder cancer in epidemiologic studies (4,5). A recent study has shown a positive association between dietary nitrite from processed meat and bladder cancer risk (6).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrosamines have been shown to cause a wide range of tumors, including cancer of the bladder, in more than 40 animal species (3). Intake of red meat (the most important source of heme iron) has shown inconsistent results with bladder cancer in epidemiologic studies (4,5). A recent study has shown a positive association between dietary nitrite from processed meat and bladder cancer risk (6).…”
Section: Introductionmentioning
confidence: 99%
“…and wide range of meat and processed meat consumption that may lead to measurement errors [24]. For example, in a study higher meat intake was evident in higher intake of energy and alcohol [19]. The same was also noted with high red meat intake and older men who were ever smokers, heavy smokers and high energy takers [7;13].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Larsson et al showed no association while an earlier case-control study showed that the consumption of fried meat, pork and sausages were associated with increased risk of developing BCa (OR=1.4, 95% CI=1.0-1.8) [19]. One study from Canada showed significantly increased risk between BCa and high intake of total meat (OR=1.6, 95% CI=1.…”
Section: Bca and Meatmentioning
confidence: 93%
See 1 more Smart Citation
“…Whereas the EPIC prospective study reported null results (Jakszyn et al, 2011), the study by Michaud et al showed an increased risk of bladder cancer associated with bacon intake (Michaud et al, 2006). A third prospective study on meat intake and risk of bladder cancer displayed again null results on the effect of meat consumption (Larsson et al, 2009).…”
Section: Discussionmentioning
confidence: 96%